Clinical and molecular characteristics of early-onset vs average-onset esophagogastric cancer - Lumish, Melissa A; Walch, Henry; Maron, Steven B; Chatila, Walid; Kemel, Yelena; Maio, Anna; Ku, Geoffrey Y; Ilson, David H; Won, Elizabeth; Li, Jia; Joshi, Smita S; Gu, Ping; et al. (JNCI : Journal of the National Cancer Institute, 2024)
The rate of esophagogastric cancer is rising among individuals under 50 years of age. It remains unknown whether early-onset esophagogastric cancer represents a unique entity. This study investigated the clinical and molecular characteristics of early-onset and average-onset esophagogastric cancer . We reviewed the Memorial Sloan Kettering Cancer Center gastric, esophageal, and gastroesophageal junction cancer database. Associations between baseline characteristics and tumor and germline molecular alterations were compared between those with early-onset and average-onset esophagogastric cancer using Fisher exact tests and the Benjamini-Hochberg method for multiple-hypothesis correction. We included 1123 patients with early-onset esophagogastric cancer (n = 219; median age = 43 years [range = 18-49 years]) and average-onset esophagogastric cancer (n = 904; median age = 67 years [range = 50-94 years]) treated between 2005 and 2018. The early-onset group had more women (39% vs 28%, P = .002). Patients with early-onset esophagogastric cancer were more likely to have a gastric primary site (64% vs 44%, P < .0001). The signet ring cell and/or diffuse type was 3 times more common in the early-onset esophagogastric cancer group (31% vs 9%, P < .0001). Early-onsite tumors were more frequently genomically stable (31% vs 18%, P = .0002) and unlikely to be microsatellite instability high (2% vs 7%, P = .003). After restricting to adenocarcinoma and signet ring cell and/or diffuse type carcinomas, we observed no difference in stage (P = .40) or overall survival from stage IV diagnosis (median = 22.7 vs 22.1 months, P = .78). Our study supported a preponderance of gastric primary disease sites, signet ring histology, and genomically stable molecular subtypes in early-onset esophagogastric cancer. Our findings highlight the need for further research to define the underlying pathogenesis and strategies for early detection and prevention.